IMPLEMENTASI KEGIATAN MENANAM SAYUR DALAM PEMBELAJARAN SAINS PADA ANAK USIA DINI DIEDUWISATA NDALEM KERTO - Cahya Mutiara Anisa; Betty Yulia Wulansari (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this study was to find out the implementation of vegetable growing activities in science learning in early childhood at the ndalem kerto tour. This study uses qualitative methods with data collection techniques obtained using observation and interview techniques. Based on the results of the research that planting vegetables can provide children with understanding related to science learning, namely the biological science of plant reproduction, the biological science that plants are living things that need food, and the biological science that plants need sunlight to grow.